DFT analysis of the [3 + 2] heterocyclization reaction of ((1,2,4-triazole(1,3,4-oxadiazole)-3(2)-yl)methyl)thiopyrimidines - Karpenko, Yu. V.; Карпенко, Юрій Вікторович (Запорізький державний медико-фармацевтичний університет, 2025)
The aim of this work is to perform a DFT analysis of the heterocyclization reaction of ((1,2,4-triazole(1,3,4-oxadiazol)-3(2)-yl)methyl) thiopyrimidines and to evaluate the stability of the transition states, as well as the influence of substituents on the activation energy. Materials and methods. 1H and 13C NMR spectra were recorded on a Bruker AC-500 spectrometer (500 MHz and 125 MHz, respectively) in DMSO-d6, using TMS as the internal standard (Agilent Technologies, Santa Clara, California, USA). LC-MS analysis was performed using an Agilent 1260 Infinity HPLC System equipped with a diode-array detector and proton ionization. Elemental analysis (C, H, N, S) was conducted on an ELEMENTAR vario EL cube, with sulfanilamide as the standard. Melting points were determined using the capillary method on a Stanford Research Systems Melting Point Apparatus 100 (SRS, USA). The reagents were sourced from Sigma-Aldrich (Merck). All calculations were performed using the molecular visualization program GaussView 5.0.8 and the Gaussian 09 Rev E.01 software package. Results. This article presents the results of a study on the mechanisms of [3 + 2] and [4 + 1] heterocyclization for the synthesis of 1,2,4-triazole and 1,3,4-oxadiazole derivatives. The reaction stages are analyzed in detail, including the formation of intermediates and cyclization, culminating in aromatization and the formation of stable heterocyclic structures. Thermodynamic analysis was conducted using the Gaussian 09 software package, incorporating calculations of enthalpy, entropy, and Gibbs free energy in both the gas phase and ethanol medium. The resulting energy profiles illustrate the key stages of the reactions and define the temperature conditions required for their execution. Special attention is given to the role of the solvent and other factors influencing process efficiency. Мета роботи – здійснити DFT-aналіз реакції гетероциклізації ((1,2,4-тріазол(1,3,4-оксадіазол)-3(2)-іл)метил)тіопіримідинів, оцінити стабільність перехідних станів і вплив замісників на енергію активації. Матеріали і методи. Спектри ЯМР 1Н і 13С записували на спектрометрі Bruker AC-500 (500 МГц і 125 МГц відповідно) в ДМСО-d6, використовуючи ТМС як внутрішній стандарт (Agilent Technologies, Санта-Клара, Каліфорнія, США). Аналіз LC-MS здійснили на системі HPLC Agilent 1260 Infinity з діодним детектором, використали протонну іонізацію. Елементний аналіз (C, H, N, S) виконали на ELEMENTAR vario EL cube із сульфаніламідом як стандартом. Температуру плавлення визначали капілярним методом на апараті Stanford Research Systems Melting Point Apparatus 100 (SRS, США). Реагенти придбано у Sigma-Aldrich (Merck). Усі обрахунки здійснили за допомогою програми візуалізації молекулярної ланки Gauss-View 5.0.8 і програмного пакета Gaussian 09 Revesio-A.02-SMP. Результати. Наведено результати дослідження механізмів [3 + 2] і [4 + 1] гетероциклізації для синтезу похідних 1,2,4-тріазолу та 1,3,4-оксадіазолу. Детально розглянуто стадії реакції, включаючи утворення проміжних продуктів і циклізацію, що завершується ароматизацією та утворенням стабільних гетероциклічних структур. Виконали термодинамічний аналіз за допомогою програмного пакета Gaussian 09, зокрема обчислення ентальпії, ентропії та енергії Гіббса в газовій фазі й етанольному середовищі. Отримані енергетичні профілі ілюструють ключові етапи реакцій і визначають температурні умови їхньої реалізації. Особливу увагу приділено ролі розчинника та інших факторів, що впливають на ефективність процесів.
DFT-aналіз реакції [3 + 2] гетероциклізації ((1,2,4-тріазол(1,3,4-оксадіазол)-3(2)-іл)метил)тіопіримідинів
Keywords: 1,2,4-triazole; 1,3,4-oxadiazole; DFT-analysis of the reaction; [3 + 2] heterocyclization; [4 + 1] heterocyclization; 1,2,4-тріазол; 1,3,4-оксадіазол; DFT-аналіз реакції; [3+2] гетероциклізація; [4+1] гетероциклізація